The genome sequence of the Stable Fly, Stomoxys calcitrans (Linnaeus, 1758) [version 1; peer review: 2 approved] - Olga Sivell; Chris Raper; Ian Sims (Wellcome Open Research)
We present a genome assembly from an individual specimen of Stomoxys calcitrans (Stable Fly; Arthropoda; Insecta; Diptera; Muscidae). The genome sequence has a total length of 1,070.90 megabases. Most of the assembly (98.96%) is scaffolded into 5 chromosomal pseudomolecules.The mitochondrial genome has also been assembled and is 17.6 kilobases in length. Gene annotation of this assembly on Ensembl identified 15,757 protein-coding genes.